История пишется объективом: [Фотокнига] / Л. Ф. Волков-Ланнит - Волков-Ланнит Леонид Филиппович (Планета, 1980)
Экземпляры: ФО-15 (1981) / Инвентарный номер: 204 / Сис.шифр: 77 / Авт.знак: В67 / ББК: 77